Optimizing transparency for users in social networking sites. Issue 6 (19th August 2014) - Wauters, Ellen; Donoso, Verónica; Lievens, Eva
Abstract : Purpose: It is the aim of this article to reflect on possible ways to optimize current ways to deliver information provision in order to make it more transparent to users In particular, we will refer to the benefits (and challenges) of employing more user-centred approaches to inform users in a more transparent way Design/methodology/approach: In this paper we analyse individual as well as contextual factors (e.g. cognitive differences, time constraints, specific features of SNS platforms) which may have an impact on the way users deal with Terms of Use, privacy policies and other types of information provision typically made available on SNS platforms. In addition, we discuss possible ways of improving current practices in the field. In particular, we refer to the benefits (and challenges) of a user-centred approach when it comes to informing users in a way that is more meaningful to them. Finally, we discuss how user-centred approaches can act as mechanisms to increase transparency in SNS environments and how (alternative) forms of regulation could benefit from such an approach. Findings: We believe that it is necessary to start focusing on users/consumers` needs, expectations and values in order to develop visualisation tools that can help make law (more) meaningful to users/consumers by giving them a better insight into their rights and obligations and by guiding them in making truly informed decisions regarding their online choices and behaviour Originality/value: By looking at different techniques such as visual design and the timing of information, the article contributes to the discussion on how we can make people more aware of legal documents and actually read them.